If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27p = 14 + -25p Solving -27p = 14 + -25p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '25p' to each side of the equation. -27p + 25p = 14 + -25p + 25p Combine like terms: -27p + 25p = -2p -2p = 14 + -25p + 25p Combine like terms: -25p + 25p = 0 -2p = 14 + 0 -2p = 14 Divide each side by '-2'. p = -7 Simplifying p = -7
| 2-12=-2x+Y | | 15x-5+125=180 | | -9(5+7y)=17 | | 18d=11d-49 | | -5/8*(-6/15) | | 29*x*a=3770 | | 3t+20=-2t | | -5/8(-6/15) | | -5x+3=7x-105 | | v(x)=x(40-2x)(30-2x) | | 11y=6+10y | | 5(3-2x)=-35 | | -3x-3(2x)=21 | | y(4y-7)=0 | | 2x-40=25 | | Y=-x^2-5.5x+1 | | -32d+28=18 | | 1/8x-5/2 | | x+1=-59-5x | | -32+28=18 | | 39=14-5m | | X+.0665X= | | 3x-6=-17+4x | | 12z-21=3z+9 | | 1/2y-15=12 | | 8+6x=-6x-100 | | 19=j+4 | | 4a-11=13 | | 38y+16-8=33 | | 1x(1x(45-40))= | | 7y+27=125 | | 4=24-56 |